Fractional dynamics and control of heat diffusion systems - Jesus, Isabel S. (2019)
In this paper we study a heat diffusion system on a fractional calculus perspective. Bearing theses ideas in mind, several fractional PID tuning methodologies are investigated and compared. The simulations demonstrate the good performance of the proposed fractional-order algorithm.